Exploring the use of Facebook and other social media sites in pre-service teacher education - Nagaletchimee Annamalai (The English Teacher, 2018)
This study investigated the use of Facebook and other social media sites in three Malaysian teachers’ training colleges. The participants were six Malaysian ESL instructors and six pre- service teachers. The six instructors were given the flexibility to use Facebook or any other social networking sites to carry out their teaching and learning activities for the Degree in English programme. Data were gathered from instructors’ reflections to identify their preferred social networking sites. It was found that the instructors were not keen to use Facebook but preferred WhatsApp, Canvas and emails for their asynchronous discussions. Focus group interviews were also conducted with pre-service teachers to identify the emerging themes. The findings have several pedagogical and research implications in using social networking sites in educational contexts.
Keywords: social media, online collaborations, online interactions